ANALISIS PENGARUH AFFECTIVE COMMITMENT, CONTINUANCE COMMITMENT, DAN NORMATIVE COMMITMENT TERHADAP KINERJA PEGAWAI ADMINISTRASI FAKULTAS EKONOMI UNIVERSITAS TANJUNGPURA PONTIANAK - B11212028, AHMAD NURROHIM (Universitas Tanjungpura, 2014)
This study was conducted to determine the effect of organizational commitment ( Affective commitment, continuance commitment , and Normative Commitment ) on the performance of employees at the Faculty of Economics, University Tanjungpura Pontianak . The population in this study is the administrative officer of the Faculty of Economics Untan totaling 31 people. Analytical tool in this study is multiple linear regression. That the results of this study variables of affective commitment (X1), continuance commitment (X2), and normative commitment (X3) has a positive and significant impact on employee performance variables Faculty of Economics Untan Economics . Based on testing coefficient of determination (R2) found that employee performance variables Faculty of Economics Untan can be explained by the variable affective commitment (X1), continuance commitment (X2), and normative commitment (X3) amounted to 73.7%, while the remaining 26,3% can be explained by other variables not examined in this study, such as personality, demographic characteristics, motivation, leadership styles and others. Â Keywords : Affective Commitment, Continuance Commitment, and Normative Commitment, Work Performance